DAMPAK PANDEMI COVID-19 TERHADAP LOYALITAS PELANGGAN PADA MCDONALD’S CABANG SHINTA KARAWACI - Andres Dharma Nurhalim (Jurnal Bina Manajemen, 2021)
The fast food industry is one of the sectors affected by the COVID-19 pandemic. The prohibition of large-scale social interaction in the community, such as holding meetings during the Large-Scale Social Restrictions (PSBB) established by each region, also contributed to a sharp decline in food and beverage sales. The average result of the COVID-19 pandemic impact variable questionnaire (X) at McDonald's Shinta Karawaci Branch was 68% in the good category. Of all the indicators of the statement, it can be seen that the lowest indicator is "Is the pandemic affecting your income" with a result of 52%, which can be seen from the general description of the respondents of McDonald's customers at Shinta Karawaci Branch, most of whom are private employees. The average result of the questionnaire total Customer Loyalty (Y) at McDonald's Shinta Karawaci Branch is 71.8% which is included in the good category. Of all these indicators, there is one indicator that has the smallest value, namely "Customers have a desire to recommend McDonald's Shinta Karawaci Branch to others". From the results of observations and interviews conducted, this is caused by several factors, one of which is the price of products offered by McDonald's Shinta Karawaci Branch which is in the upper middle category and Shinta Karawaci Branch's McDonald's outlets are still not evenly distributed, there are only a few in the city center. big. From the results of simple linear regression analysis, it is known that the influence of variable X for the COVID-19 pandemic has no effect on customer loyalty at McDonald's Shinta Karawaci Branch, variable Y.